Bi2O2S-based photocatalytic material as well as preparation method and application thereof

Through the introduction of oxygen empty positions and constructing S-type heterogeneous knots on BI2O2S, the OV-BI2O2S/BI4O5I2 composite photocatalytic material is formed, which solve the problem of loading of BI2O2S catalyst in the photocatalytic application, and achieve efficient hydrogen peroxide synthesis.

CN119368202AActive Publication Date: 2025-01-28HOHAI UNIV +1

Patent Information

Application Number
CN202411624158.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing semiconductor photocatalytic technology has low yields when preparing hydrogen peroxide, and Bi2O2S catalysts encounter rapid carrier recombination problems in photocatalytic applications, resulting in insufficient photocatalytic activity.

Method used

By introducing oxygen air levels (OV) on BI2O2S and constructing S-shaped heterogeneous knots, OV-BI2O2S/BI4O5I2 composite photocatalytic materials are formed, increasing the density of load sub-density and migration rate, and improving the optical catalytic performance.

Benefits of technology

The load density and migration rate of OV-BI2O2S/BI4O5I2 photocatalytic materials have been increased, the photocatalytic activity is enhanced, and the effective separation of light capture capabilities and light-induced carrier flowing under the wide light spectrum can achieve efficient peroxidation Hydrogen synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368202A_ABST
    Figure CN119368202A_ABST
Patent Text Reader

Abstract

The invention provides a photocatalytic material based on Bi2O2S and a preparation method and application of the photocatalytic material based on Bi2O2S, the structure of the photocatalytic material based on Bi2O2S comprises Bi2O2S, oxygen vacancies introduced on the Bi2O2S and an S-type heterojunction constructed on the Bi2O2S; the photocatalytic material based on Bi2O2S is an OV-Bi2O2S / Bi4O5I2 composite photocatalytic material, and the Bi2O2S / Bi4O5I2 composite photocatalytic material is a Bi2O2S / The preparation method of the OV-Bi2O2S / Bi4O5I2 composite photocatalytic material.The preparation method of the OV-Bi2O2S / Bi4O5I2 composite photocatalytic material.The preparation method of the OV-Bi2O2S / Bi4O5I2 composite photocatalytic material.The OV-Bi2O2S / Bi4O5I2 composite photocatalytic material is suitable for hydrogen peroxide synthesis.The preparation method of the OV-Bi2O2S / Bi4O5I2 composite photocatalytic material is a novel composite photocatalytic material novel in structure and excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Bi2O2S-based photocatalytic material and a preparation method and application thereof, belonging to the technical field of photocatalytic materials. Background Art

[0002] Hydrogen peroxide is considered to be an important industrial chemical raw material due to its oxidation / reduction properties, eco-friendliness, and high energy release. Its applications involve pulp bleaching, environmental remediation, liquid propellants, disinfection and other fields. In recent years, hydrogen peroxide has also shown great potential to replace hydrogen power generation in single-chamber batteries due to its liquid form, storability and high safety.

[0003] Currently, hydrogen peroxide is mainly produced through the anthraquinone method, but the traditional anthraquinone method has disadvantages such as high energy consumption and emission of a large amount of toxic by-products; therefore, finding a low-energy, environmentally friendly method for producing hydrogen peroxide has received widespread attention; since semiconductor photocatalytic technology only requires H2O, O2 and light energy, and also has the advantages of being pollution-free and having abundant reserves, it is considered to be one of the most promising H2O2 synthesis technologies, but the current problem of low yield of hydrogen peroxide prepared by semiconductor photocatalytic technology still needs to be solved urgently.

[0004] Among semiconductor photocatalytic materials, low-dimensional bismuth oxysulfide (Bi2O2S) has attracted extensive attention in the fields of electronics and optoelectronics due to its outstanding stability, high carrier mobility and unique structure; despite the fascinating interplay between internal electrostatic fields and nonequilibrium carrier properties, Bi2O2S encounters difficulties in photocatalytic applications due to its rapid carrier recombination.

[0005] The introduction of oxygen vacancies (O V ) and the establishment of heterojunctions can effectively adjust the band structure and light absorption ability of Bi2O2S, thereby improving the adsorption and activation of O2 molecules; for example, Chinese invention patent application No. 202311229674.4 discloses a Bi2O2S / Bi 12 TiO 20 Preparation method and application of composite photocatalytic materials, but Bi2O2S / Bi 12 TiO 20 The heterojunction is affected by the strain field and structural defects caused by lattice mismatch, resulting in poor interface quality; Chinese invention patent application No. 202010967455.6 discloses a Co-doped Bi2O2S catalyst and its preparation method and application, but the Co-doped Bi2O2S catalyst has disadvantages such as narrow band structure, low light absorption capacity, and rapid carrier recombination, and there are still problems such as insufficient photocatalytic activity. Summary of the invention

[0006] The present invention provides a photocatalytic material based on Bi2O2S and a preparation method and application thereof, the purpose of which is to enhance the photocatalytic activity of the Bi2O2S catalyst.

[0007] The technical solution of the present invention is a photocatalytic material based on Bi2O2S, the structure of which includes Bi2O2S, oxygen vacancies introduced on the Bi2O2S, and an S-type heterojunction constructed on the Bi2O2S.

[0008] The Bi2O2S-based photocatalytic material is O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

[0009] Further, the O V -The preparation method of Bi2O2S / Bi4O5I2 composite photocatalytic material comprises: Step 1) Preparation of O V -Bi2O2S catalyst; Step 2) Preparation of O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

[0010] Furthermore, the step 1) prepares O V -Bi2O2S, specifically including: Step 1-1) dissolving thiourea and bismuth nitrate in distilled water and stirring to form a mixed solution of thiourea and bismuth nitrate, then adding lithium hydroxide to the mixed solution of thiourea and bismuth nitrate and stirring to form a first mixture; Step 1-2) transferring the first mixture to a heating container for heating, washing the mixture after heating and drying it to obtain Bi2O2S; Step 1-3) calcining Bi2O2S under nitrogen atmosphere to obtain O V -Bi2O2S.

[0011] Furthermore, in step 2) preparing O V -Bi2O2S / Bi4O5I2 composite photocatalytic material, specifically including: Step 2-1) adding bismuth nitrate to the mannitol solution and stirring to form a bismuth nitrate solution; Step 2-2) The O prepared in step 1) V -Bi2O2S is added to the bismuth nitrate solution; Step 2-3) Potassium iodide is added to the mannitol solution and stirred to form a potassium iodide solution, and then the potassium iodide solution is added dropwise to the above-mentioned solution containing O V -Bi2O2S in a bismuth nitrate solution and adjusting the pH with sodium hydroxide to form a second mixture; Step 2-4) The second mixture is then transferred to a heating container for heating, washed and dried to obtain O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

[0012] Furthermore, in the step 1-1), the mass concentrations of thiourea and bismuth nitrate dissolved in distilled water are 2.2 g / L to 2.8 g / L and 30 g / L to 35 g / L, respectively; in the step 1-1), the mass volume ratio of lithium hydroxide to the mixed solution of thiourea and bismuth nitrate is 35 g / L to 45 g / L; in the step 1-2), when the first mixture is transferred to a heating container for heating, the heating temperature is 200°C to 220°C and the heating time is 68h to 72h; in the step 1-3), when Bi2O2S is calcined under a nitrogen atmosphere, the calcination temperature is 380°C to 400°C and the calcination time is 2h to 4h.

[0013] Furthermore, the mass concentration of mannitol in the mannitol solution in step 2-1) and step 2-3) is preferably 15 g / L to 20 g / L; in step 2-4), the second mixture is transferred to a heating container for heating at a temperature of 120°C to 140°C and a heating time of 20h to 24h; in step 2-4), the O V -Bi2O2S / Bi4O5I2 photocatalytic material, the drying temperature is 60℃~80℃, and the drying time is 10h~12h.

[0014] Furthermore, in step 2-1), the mass volume ratio of bismuth nitrate to mannitol solution is 45 g / L to 50 g / L; in step 2-2), O V -The mass volume ratio of Bi2O2S to bismuth nitrate solution is 5 g / L to 15 g / L; the mass volume ratio of potassium iodide to mannitol solution in step 2-3) is preferably 15 g / L to 20 g / L; the pH of the second mixture formed after adjusting the pH with sodium hydroxide in step 2-3) is 9 to 11.

[0015] Further, the O V -Bi2O2S / Bi4O5I2 composite photocatalytic material is suitable for hydrogen peroxide synthesis; the O V -Application of Bi2O2S / Bi4O5I2 composite photocatalytic material in hydrogen peroxide synthesis, specifically including: V -Bi2O2S / Bi4O5I2 composite photocatalytic material was added to deionized water containing glycerol, stirred in the dark at room temperature and injected with oxygen to achieve adsorption equilibrium, and then reacted for a certain period of time under visible light irradiation and oxygen supply conditions.

[0016] Further, the OV -The ratio of Bi2O2S / Bi4O5I2 composite photocatalytic material added to deionized water containing glycerol is 0.2 g / L to 0.8 g / L; the volume ratio of glycerol to deionized water in the deionized water containing glycerol is 1:30 to 1:10; the reaction time under visible light irradiation and oxygen supply conditions is 20 minutes to 60 minutes.

[0017] Beneficial effects of the present invention: 1) O prepared by the present invention V -Bi2O2S / Bi4O5I2 photocatalytic materials, by introducing oxygen vacancies, inject additional delocalized electrons into the conduction band, thereby increasing the O V -Carrier density and mobility of Bi2O2S / Bi4O5I2 photocatalytic materials; 2) Due to O V -Bi2O2S and Bi4O5I2 form an S-type heterojunction with strong interface interaction, which is beneficial to the transport of photogenerated carriers between the composites, can inhibit the recombination of photogenerated electron-hole pairs, and improve the photocatalytic activity; 3) O V -Bi2O2S / Bi4O5I2 photocatalytic materials have localized electronic states (composed of Bi6p orbitals), and electrons are directly excited into the conduction band, so they can exhibit excellent light capture ability and effective separation of photoinduced carriers in a wide spectrum, thereby improving the O V -Photocatalytic performance of Bi2O2S / Bi4O5I2 photocatalytic materials; 4) O prepared by the present invention V -Bi2O2S / Bi4O5I2 photocatalytic material has the advantages of green economy, good stability and high catalytic activity. It is a new type of composite photocatalytic material with novel structure and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Attached Figure 1 O prepared in Example 5 V -SEM image of Bi2O2S / Bi4O5I2.

[0019] Attached Figure 2 O prepared in Example 5 V -TEM image of Bi2O2S / Bi4O5I2.

[0020] Attached Figure 3 O prepared in Example 5 V -HRTEM image of Bi2O2S / Bi4O5I2.

[0021] Attached Figure 4 Pure Bi2O2S (prepared in Example 1), OV -Bi2O2S (prepared in Example 2), Bi4O5I2 (prepared in Example 3), O V -XRD pattern of Bi2O2S / Bi4O5I2 (prepared in Examples 4, 5, and 6) composite visible light photocatalytic material.

[0022] Attached Figure 5 The pure Bi2O2S of the present invention (prepared in Example 1), O V -Bi2O2S (prepared in Example 2), Bi4O5I2 (prepared in Example 3), O V -Comparison of the efficiency of Bi2O2S / Bi4O5I2 (prepared in Examples 4, 5, and 6) composite visible light catalytic materials in producing hydrogen peroxide under visible light conditions.

[0023] Attached Figure 6 For the present invention V -Bi2O2S (S2 prepared in Example 2), Bi4O5I2 (S3 prepared in Example 3), O V -Ultraviolet-visible diffuse reflectance spectrum of Bi2O2S / Bi4O5I2 (S5 prepared in Example 5) composite visible light catalytic material.

[0024] Attached Figure 7 For the present invention V -Bi2O2S (S2 prepared in Example 2), Bi4O5I2 (S3 prepared in Example 3), O V -Photoluminescence spectrum of Bi2O2S / Bi4O5I2 (S5 prepared in Example 5) composite visible light catalytic material. DETAILED DESCRIPTION

[0025] A Bi2O2S-based photocatalytic material, the structure of which includes Bi2O2S, oxygen vacancies introduced on the Bi2O2S, and an S-type heterojunction constructed on the Bi2O2S.

[0026] The Bi2O2S-based photocatalytic material is O V -Bi2O2S / Bi4O5I2 composite photocatalytic material; the O V -Bi2O2S / Bi4O5I2 composite photocatalytic material increases O by introducing oxygen vacancies and constructing S-type heterojunction V -Bi2O2S / Bi4O5I2 composite photocatalytic material carrier density and mobility; at the same time, O V -Bi2O2S / Bi4O5I2 has a strong interface interaction, which is beneficial to the transport of photogenerated carriers between the composites, can inhibit the recombination of photogenerated electron-hole pairs, and improve the photocatalytic activity.

[0027] AV - A method for preparing a Bi2O2S / Bi4O5I2 composite photocatalytic material, the method comprising the following steps: Step 1) Preparation of O V -Bi2O2S catalyst; Step 2) Preparation of O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

[0028] Step 1) preparing O V -Bi2O2S, specifically comprising the following steps: Step 1-1) dissolving thiourea and bismuth nitrate in distilled water and stirring to form a mixed solution of thiourea and bismuth nitrate, then adding lithium hydroxide to the mixed solution of thiourea and bismuth nitrate and stirring to form a first mixture; Step 1-2) transferring the first mixture to a heating container for heating, washing the mixture after heating and drying it to obtain Bi2O2S; the heating container is preferably a 100 mL polytetrafluoroethylene-lined autoclave; Step 1-3) calcining Bi2O2S under nitrogen atmosphere to obtain O V -Bi2O2S; preferably Bi2O2S is calcined in a tube furnace under a nitrogen atmosphere to obtain O V -Bi2O2S.

[0029] Step 2) Preparation of O V -Bi2O2S / Bi4O5I2 composite photocatalytic material, specifically comprising the following steps: Step 2-1) adding bismuth nitrate to a mannitol solution and stirring to form a bismuth nitrate solution; wherein the mass volume ratio of bismuth nitrate to mannitol solution is preferably 45 g / L to 50 g / L, that is, 45 g to 50 g of bismuth nitrate is added to every 1 L of mannitol solution; Step 2-2) The O prepared in step 1) V -Bi2O2S was added to bismuth nitrate solution and stirred magnetically; among them, O V The mass volume ratio of Bi2O2S to bismuth nitrate solution is 5 g / L to 15 g / L, that is, 5 g to 15 g of O-Bi2O2S is added to every 1 L of bismuth nitrate solution. V -Bi2O2S; Step 2-3) adding potassium iodide to the mannitol solution and stirring to form a potassium iodide solution, and then slowly adding the ultrasonically stirred potassium iodide solution dropwise to the above-mentioned solution containing O V-Bi2O2S bismuth nitrate solution, ultrasonically stirred, and adjusted the pH with sodium hydroxide to form a second mixture; wherein the mass volume ratio of potassium iodide to mannitol solution is preferably 15g / L to 20g / L, that is, 15g to 20g of potassium iodide is added to every 1L of mannitol solution; Step 2-4) The second mixture is then transferred to a heating container for heating, washed and dried to obtain O V -Bi2O2S / Bi4O5I2 composite photocatalytic material; the heating container is preferably a 100 mL polytetrafluoroethylene-lined autoclave.

[0030] In the step 1-1), the mass concentrations of thiourea and bismuth nitrate dissolved in distilled water are 2.2 g / L to 2.8 g / L and 30 g / L to 35 g / L, respectively, that is, 2.2 g to 2.8 g of thiourea and 30 g to 35 g of bismuth nitrate are dissolved in every 1 L of distilled water.

[0031] In the step 1-1), the mass volume ratio of lithium hydroxide to the mixed solution of thiourea and bismuth nitrate is 35 g / L to 45 g / L, that is, 35 g to 45 g of lithium hydroxide is added to every 1 L of the mixed solution of thiourea and bismuth nitrate.

[0032] In the step 1-2), when the first mixture is transferred to a heating container for heating, the heating temperature is preferably 200° C. to 220° C., and the heating time is preferably 68 h to 72 h.

[0033] In the step 1-3), when Bi2O2S is calcined under a nitrogen atmosphere, the calcination temperature is preferably 380°C to 400°C, and the calcination time is preferably 2h to 4h.

[0034] In the step (2), the stirring and magnetic stirring times are preferably 10 min to 30 min, and the ultrasonic stirring time is preferably 20 min to 40 min.

[0035] The mass concentration of mannitol in the mannitol solution in step 2-1) and step 2-3) is preferably 15 g / L to 20 g / L.

[0036] The pH of the second mixture formed by adjusting the pH with sodium hydroxide in step 2-3) is preferably 9-11, and more preferably 10.

[0037] In the step 2-4), when the second mixture is transferred to a heating container for heating, the heating temperature is preferably 120° C. to 140° C., and the heating time is preferably 20 h to 24 h.

[0038] In the step 2-4), after washing and drying, O V-Bi2O2S / Bi4O5I2 photocatalytic material, the drying temperature is preferably 60°C to 80°C, and the drying time is preferably 10h to 12h.

[0039] The O V -Bi2O2S / Bi4O5I2 composite photocatalytic material is suitable for hydrogen peroxide synthesis.

[0040] A V -Application of Bi2O2S / Bi4O5I2 composite photocatalytic material in hydrogen peroxide synthesis, specifically including: V -Bi2O2S / Bi4O5I2 composite photocatalytic material was added to deionized water containing glycerol, stirred in the dark at room temperature and injected with oxygen to achieve adsorption equilibrium, and then reacted for a certain period of time under visible light irradiation and oxygen supply conditions.

[0041] The O V -The ratio of Bi2O2S / Bi4O5I2 composite photocatalytic material added to deionized water containing glycerol is preferably 0.2 g / L to 0.8 g / L, that is, 0.2g to 0.8g of composite photocatalytic material is added to every 1L of deionized water containing glycerol; the volume ratio of glycerol to deionized water in the deionized water containing glycerol is preferably 1:30 to 1:10; the reaction time under visible light irradiation and oxygen supply conditions is preferably 20min to 60min.

[0042] The mechanism of the present invention is: V The existence of V - The localized electronic states below the conduction band of Bi2O2S (composed of Bi6p orbitals) promote the direct excitation of localized electrons to O V -In the conduction band of Bi2O2S; O V It can act as an electron donor to inject additional delocalized electrons into the conduction band, thereby increasing the carrier density and mobility. V During the formation of the S-type heterojunction between Bi2O2S and Bi4O5I2, electrons migrate from Bi4O5I2 to O V -Bi2O2S, when O V When the Bi2O2S surface reaches equilibrium, an electron depletion layer is formed on the surface, and at the same time, an electron accumulation layer is formed on the Bi4O5I2 surface near the interface; the electron loss leads to the formation of O V -Bi2O2S energy band bends upward, while Bi4O5I2 energy band bends downward; at the same time, Bi4O5I2 and O V The internal electric field between Bi2O2S separates electron-hole pairs with high redox ability more quickly; then, under visible light, the photogenerated electrons easily move from the CB (conduction band) of Bi4O5I2 to OV -VB (valence band) of Bi2O2S; therefore, the electrons interact with dissolved O2 in water to produce H2O2.

[0043] The Bi2O2S-based photocatalytic material prepared in the present invention overcomes the shortcomings of the prior art, such as poor interface quality, narrow energy band structure, low light absorption capacity, and rapid carrier recombination. V -Bi2O2S / Bi4O5I2 composite photocatalytic material, by introducing oxygen vacancies and constructing S-type heterojunction, thereby increasing O V -Bi2O2S / Bi4O5I2 composite photocatalytic material carrier density and mobility; at the same time, O V -Bi2O2S / Bi4O5I2 has a strong interface interaction, which is beneficial to the transport of photogenerated carriers between the composites, can inhibit the recombination of photogenerated electron-hole pairs, and improve the photocatalytic activity.

[0044] The present invention is described in detail below in conjunction with examples so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following examples; in the following examples, unless otherwise specified, the materials and instruments used are commercially available, and the equipment used is conventional equipment. Example 1

[0045] Thiourea and bismuth nitrate were dissolved in distilled water and stirred to form a mixed solution of thiourea and bismuth nitrate. The mass concentrations of thiourea and bismuth nitrate to distilled water were 2.53 g / L and 32.4 g / L, respectively, that is, 2.53 g thiourea and 32.4 g bismuth nitrate were dissolved in 1 L of distilled water, respectively. The mass volume ratio of lithium hydroxide in the mixed solution of thiourea and bismuth nitrate was 40 g / L. Subsequently, lithium hydroxide was added to the mixed solution of thiourea and bismuth nitrate and stirred. After stirring, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 200°C for 72 h. After washing, it was dried to obtain Bi2O2S (labeled as S1). Example 2

[0046] The Bi2O2S catalyst prepared in Example 1 was calcined at 400°C for 4 h in a tubular furnace under a nitrogen atmosphere to prepare O V -Bi2O2S catalyst (labeled as S2). Example 3

[0047] Bismuth nitrate is added to a mannitol solution and stirred to form a bismuth nitrate solution, wherein the mass volume ratio of bismuth nitrate to mannitol solution is 48.5 g / L; potassium iodide is added to the mannitol solution and stirred for 20 min to form a potassium iodide solution, and ultrasonically stirred for 30 min, and then the ultrasonically stirred potassium iodide solution is slowly added dropwise to the above bismuth nitrate solution, and ultrasonically stirred for 30 min, and sodium hydroxide is used to adjust the pH to 10 to form a mixture; wherein the mass volume ratio of potassium iodide to mannitol solution in the potassium iodide solution is preferably 16.6 g / L; the mass concentration of mannitol in the mannitol solution used is 18.2 g / L; and then the mixture is transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 140°C for 24 h, washed and dried at 60°C to obtain Bi4O5I2 (labeled as S3). Example 4

[0048] Bismuth nitrate was added to the mannitol solution and stirred to form a bismuth nitrate solution, wherein the mass volume ratio of bismuth nitrate to mannitol solution was 48.5 g / L; V -Bi2O2S was added to the bismuth nitrate solution, wherein the O prepared in Example 2 V The mass volume ratio of -Bi2O2S to bismuth nitrate solution was 5 g / L; potassium iodide was added to the mannitol solution and stirred for 20 min to form a potassium iodide solution. After ultrasonic stirring for 30 min, the potassium iodide solution was slowly added dropwise to the above-mentioned solution containing O V -Bi2O2S was added to a bismuth nitrate solution and ultrasonically stirred for 30 min, and a mixture was formed after adjusting the pH to 10 with sodium hydroxide; wherein the mass volume ratio of potassium iodide in the potassium iodide solution to mannitol solution was 16.6 g / L; the mass concentration of mannitol in the mannitol solution used was 18.2 g / L; the mixture was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 140°C for 24 h, washed and dried at 60°C to obtain O V -Bi2O2S / Bi4O5I2 (labeled as S4). Example 5

[0049] Bismuth nitrate was added to the mannitol solution and stirred to form a bismuth nitrate solution, wherein the mass volume ratio of bismuth nitrate to mannitol solution was 48.5 g / L; V -Bi2O2S was added to the bismuth nitrate solution, wherein the O prepared in Example 2 V The mass volume ratio of -Bi2O2S to bismuth nitrate solution was 10 g / L; potassium iodide was added to the mannitol solution and stirred for 20 min to form a potassium iodide solution. After ultrasonic stirring for 30 min, the potassium iodide solution was slowly added dropwise to the above-mentioned solution containing O V-Bi2O2S was added to a bismuth nitrate solution and ultrasonically stirred for 30 min, and a mixture was formed after adjusting the pH to 10 with sodium hydroxide; wherein the mass volume ratio of potassium iodide in the potassium iodide solution to mannitol solution was 16.6 g / L; the mass concentration of mannitol in the mannitol solution used was 18.2 g / L; the mixture was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 140 °C for 24 h, washed and dried at 60 °C to obtain O V -Bi2O2S / Bi4O5I2 (labeled as S5). Example 6

[0050] Bismuth nitrate was added to the mannitol solution and stirred to form a bismuth nitrate solution, wherein the mass volume ratio of bismuth nitrate to mannitol solution was 48.5 g / L; V -Bi2O2S was added to the bismuth nitrate solution, wherein the O prepared in Example 2 V -Bi2O2S mass volume ratio in bismuth nitrate solution is 15 g / L; potassium iodide is added to mannitol solution and stirred for 20 min to form potassium iodide solution, and then the potassium iodide solution is slowly added dropwise to the above-mentioned solution containing O V -Bi2O2S was added to a bismuth nitrate solution and ultrasonically stirred for 30 min, and a mixture was formed after adjusting the pH to 10 with sodium hydroxide; wherein the mass volume ratio of potassium iodide in the potassium iodide solution to mannitol solution was 16.6 g / L; the mass concentration of mannitol in the mannitol solution used was 18.2 g / L; the mixture was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 140 °C for 24 h, washed and dried at 60 °C to obtain O V -Bi2O2S / Bi4O5I2 (labeled as S6).

[0051] Attached Figure 1 O prepared in Example 5 V -SEM image of Bi2O2S / Bi4O5I2, from the attached Figure 1 It can be seen that the prepared O V -Bi2O2S / Bi4O5I2 composite visible light catalytic material is in the form of nanosheets.

[0052] Attached Figure 2 O prepared in Example 5 V -TEM image of Bi2O2S / Bi4O5I2, from the attached Figure 2 It can be seen that the nanosheets have a plane spacing of 0.277 nm, corresponding to the (130) plane of Bi2O2S; in addition, the lattice spacing of 0.310 nm is attributed to Bi4O5I2, corresponding to the (-4-11) plane; V-A compact interface is formed between Bi2O2S and Bi4O5I2.

[0053] Attached Figure 3 O prepared in Example 5 V -HRTEM image of Bi2O2S / Bi4O5I2, from the attached Figure 3 It can be seen that O V The discontinuous and blurred crystal stripes of the Bi2O2S / Bi4O5I2 composite visible light photocatalytic material indicate the presence of structural defects, resulting in an incomplete and disordered lattice, confirming the enrichment of O V As the generation of active sites.

[0054] Attached Figure 4 Pure Bi2O2S (prepared in Example 1), O V -Bi2O2S (prepared in Example 2), Bi4O5I2 (prepared in Example 3), O V -Bi2O2S / Bi4O5I2 (prepared in Examples 4, 5, and 6) composite visible light photocatalytic material XRD pattern, as shown in the attached Figure 4 It can be seen that for Bi2O2S material, typical characteristic diffraction peaks are shown at 14.88°, 24.23°, 27.42°, 29.96°, 32.29°, 32.40°, 32.78° and 36.19°, corresponding to (020), (110), (120), (040), (130), (031), (101) and (121) of Bi2O2S; Bi2O2S and O V -Bi2O2S has the same peak profile; O V -Bi2O2S has a lower peak intensity and a peak shift to a higher angle than Bi2O2S, which is due to the V and structural changes caused by surface disorder; the XRD spectrum of Bi4O5I2 shows a typical diffraction peak at 28.8°, which matches the standard Bi4O5I2 crystal phase (-4-11); V -Bi2O2S / Bi4O5I2 photocatalyst, diffraction peaks can be observed, indicating that O V -Bi2O2S has been effectively doped into Bi4O5I2; V -The peak of Bi2O2S / Bi4O5I2 shifts to a higher angle relative to that of Bi4O5I2 because O V -Interface interaction between Bi2O2S material and Bi4O5I2. Example 7

[0055] Take 20 mg Bi2O2S (S1 prepared in Example 1), 20 mg O V-Bi2O2S (S2 prepared in Example 2), 20 mgBi4O5I2 (S3 prepared in Example 3), 20 mg O V -Bi2O2S / Bi4O5I2 (S4 prepared in Example 4), 20 mg O V -Bi2O2S / Bi4O5I2 (S5 prepared in Example 5) and 20 mg O V -Bi2O2S / Bi4O5I2 (S6 prepared in Example 6) were added separately to deionized water (50 mL) containing glycerol to form 6 mixed solutions for synthesizing hydrogen peroxide, wherein the volume ratio of glycerol to deionized water in the deionized water containing glycerol was 1:20. Oxygen was injected into each mixed solution for synthesizing hydrogen peroxide under dark conditions and stirred for 30 min. The obtained mixed solution was subjected to photocatalytic reaction under visible light conditions for 30 min. After the reaction, 10 μL aliquots were taken, the photocatalyst was filtered through a 0.22 μm cellulose membrane, and the productivity of H2O2 was determined by iodine titration. The results are shown as follows: Figure 5 shown.

[0056] Attached Figure 5 The pure Bi2O2S of the present invention (prepared in Example 1), O V -Bi2O2S (prepared in Example 2), Bi4O5I2 (prepared in Example 3), O V -Bi2O2S / Bi4O5I2 (prepared in Examples 4, 5, and 6) composite visible light catalytic material catalytic production of hydrogen peroxide efficiency under visible light conditions, as shown in the attached Figure 5 It can be seen that after 30 min of illumination, S5 (prepared in Example 5) of the present invention V -Bi2O2S / Bi4O5I2) has the highest efficiency in producing hydrogen peroxide under visible light conditions, which shows that the O V -Bi2O2S / Bi4O5I2 composite photocatalytic material can effectively synthesize hydrogen peroxide.

[0057] Attached Figure 6 For the present invention V -Bi2O2S (S2 prepared in Example 2), Bi4O5I2 (S3 prepared in Example 3), O V -Bi2O2S / Bi4O5I2 (S5 prepared in Example 5) composite visible light catalytic material UV-visible diffuse reflectance spectrum, by the attached Figure 6 It can be seen that S5 shows a broader light absorption spectrum than S3, which indicates that O V -Bi2O2S combined with Bi4O5I2 to form an S-type heterojunction can enhance the light absorption of the composite material; at the same time, the Tauc method was used to determine the O V-Band structures of Bi2O2S and Bi4O5I2.

[0058] Attached Figure 7 For the present invention V -Bi2O2S (S2 prepared in Example 2), Bi4O5I2 (S3 prepared in Example 3), O V -Bi2O2S / Bi4O5I2 (S5 prepared in Example 5) composite visible light catalytic material photoluminescence spectrum, by the attached Figure 7 It can be seen that the PL intensity of S5 is the lowest, indicating that O V -Bi2O2S combines with Bi4O5I2 to form an S-type heterojunction, which reduces the recombination of photogenerated carriers.

Claims

1. A photocatalytic material based on Bi2O2S, characterized in that It includes Bi2O2S, oxygen vacancies introduced on Bi2O2S, and S-type heterojunction constructed on Bi2O2S.

2. A photocatalytic material based on Bi2O2S, characterized in that The Bi2O2S-based photocatalytic material is O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

3. A Bi2O2S-based photocatalytic material according to claim 2, characterized in that The O V -The preparation method of Bi2O2S / Bi4O5I2 composite photocatalytic material comprises: Step 1) Preparation of O V -Bi2O2S catalyst; Step 2) Preparation of O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

4. A Bi2O2S-based photocatalytic material according to claim 3, characterized in that Step 1) preparing O V -Bi2O2S, specifically including: Step 1-1) dissolving thiourea and bismuth nitrate in distilled water and stirring to form a mixed solution of thiourea and bismuth nitrate, then adding lithium hydroxide to the mixed solution of thiourea and bismuth nitrate and stirring to form a first mixture; Step 1-2) transferring the first mixture to a heating container for heating, washing the mixture after heating and drying it to obtain Bi2O2S; Step 1-3) calcining Bi2O2S under nitrogen atmosphere to obtain O V -Bi2O2S.

5. The photocatalytic material based on Bi2O2S according to claim 3, characterized in that Step 2) Preparation of O V -Bi2O2S / Bi4O5I2 composite photocatalytic material, specifically including: Step 2-1) adding bismuth nitrate to the mannitol solution and stirring to form a bismuth nitrate solution; Step 2-2) The O prepared in step 1) V -Bi2O2S is added to the bismuth nitrate solution; Step 2-3) Potassium iodide is added to the mannitol solution and stirred to form a potassium iodide solution, and then the potassium iodide solution is added dropwise to the above-mentioned solution containing O V -Bi2O2S in a bismuth nitrate solution and adjusting the pH with sodium hydroxide to form a second mixture; Step 2-4) The second mixture is then transferred to a heating container for heating, washed and dried to obtain O V -Bi2O2S / Bi4O5I2 composite photocatalytic material.

6. The Bi2O2S-based photocatalytic material according to claim 4, characterized in that In the step 1-1), the mass concentrations of thiourea and bismuth nitrate dissolved in distilled water are 2.2 g / L to 2.8 g / L and 30 g / L to 35 g / L, respectively; in the step 1-1), the mass volume ratio of lithium hydroxide to the mixed solution of thiourea and bismuth nitrate is 35 g / L to 45 g / L; in the step 1-2), when the first mixture is transferred to a heating container for heating, the heating temperature is 200° C. to 220° C. and the heating time is 68 h to 72 h; in the step 1-3), when Bi2O2S is calcined under a nitrogen atmosphere, the calcination temperature is 380° C. to 400° C. and the calcination time is 2 h to 4 h.

7. The Bi2O2S-based photocatalytic material according to claim 5, characterized in that The mass concentration of mannitol in the mannitol solution in step 2-1) and step 2-3) is preferably 15 g / L to 20 g / L; in step 2-4), the second mixture is transferred to a heating container for heating at a temperature of 120°C to 140°C and a heating time of 20h to 24h; in step 2-4), the second mixture is washed and dried to obtain O V -Bi2O2S / Bi4O5I2 photocatalytic material, the drying temperature is 60℃~80℃, and the drying time is 10h~12h.

8. The Bi2O2S-based photocatalytic material according to claim 5, characterized in that In the step 2-1), the mass volume ratio of bismuth nitrate to mannitol solution is 45 g / L to 50 g / L; in the step 2-2), O V -The mass volume ratio of Bi2O2S to bismuth nitrate solution is 5 g / L to 15 g / L; the mass volume ratio of potassium iodide to mannitol solution in step 2-3) is 15 g / L to 20 g / L; the pH of the second mixture formed after adjusting the pH with sodium hydroxide in step 2-3) is 9 to 11.

9. A Bi2O2S-based photocatalytic material according to any one of claims 2 to 8, characterized in that The O V -Bi2O2S / Bi4O5I2 composite photocatalytic material is suitable for hydrogen peroxide synthesis; the O V -Application of Bi2O2S / Bi4O5I2 composite photocatalytic material in hydrogen peroxide synthesis, specifically including: V -Bi2O2S / Bi4O5I2 composite photocatalytic material was added to deionized water containing glycerol, stirred in the dark at room temperature and injected with oxygen to achieve adsorption equilibrium, and then reacted for a certain period of time under visible light irradiation and oxygen supply conditions.

10. The Bi2O2S-based photocatalytic material according to claim 9, characterized in that The O V -The ratio of Bi2O2S / Bi4O5I2 composite photocatalytic material added to deionized water containing glycerol is 0.2 g / L to 0.8 g / L; the volume ratio of glycerol to deionized water in the deionized water containing glycerol is 1:30 to 1:10; the reaction time under visible light irradiation and oxygen supply conditions is 20 minutes to 60 minutes.

Citation Information

Patent Citations

  • Co-doped Bi2O2S catalyst as well as preparation method and application thereof

    CN112452342A

  • BiOCl / Bi2O3 photocatalytic material and preparation method and application thereof

    CN112495403A

  • Preparation and application of bismuth oxysulfide-based up-conversion material composite photocatalyst

    CN113117702A

  • Bi4O5I2 / carbon boron nitride quantum dot photocatalytic material as well as preparation method and application thereof

    CN113134381A

  • Preparation of Bi4O5I2 / Bi2O2CO3 photocatalyst

    CN113877616A

Cited By

  • All-weather piezoelectric coupling photocatalyst as well as preparation method and application thereof

    CN120790186A

  • All-weather piezoelectric coupling photocatalyst and preparation method and application thereof

    CN120790186B